Does Financial Liberalization Affect Bank Risk-Taking in China?. (November 2019) - Wang, Rui; Luo, Hang (Robin)
This article examines the effect of financial liberalization on bank risk-taking, using bank-level data of 169 Chinese banks from 2000-2014. Empirical results show that bank stability increases with the development of financial liberalization. We also provide evidence indicating that banks with larger size, longer operating periods, and state ownership are more salient with the development of financial liberalization. However, such positive effects of financial liberalization on bank stability may be weakened by worse macroenvironment gauged by low economic growth, poor law enforcement, and instable political conditions.